Analysis of the Relationship Between Biology Students’ Learning Motivation and Online Learning - Roziqoh, Ati; Nahdiyatunnisa, Nahdiyatunnisa; Benliani, Naila Fatimah Azzahra; Vanza, Nabila; Sari, Indah Juwita (Jurnal Pendidikan Abad Ke-21, 2025)
Motivation to learn is an internal process that becomes one of the drivers for students to engage and direct themselves in the learning process to achieve results. To engage and direct themselves in the learning process to achieve the desired results. This study aims to analyze the relationship between biology students’ learning motivation and online learning at one of the universities in Banten, Indonesia. This research uses a descriptive correlation method through a questionnaire filling approach. The collected data were analyzed using SPSS software. The significance value of online learning and student learning motivation shows, Sig. 0.05 = Ho accepted = no difference = online learning data on learning motivation. The results of this study indicate a significant relationship between online learning and student learning motivation. This research has some limitations, such as time constraints, as well as the representation of respondents who may not cover the entire student population.